Native and Alien Ungulates in North America: Potential for Restoring Herbivore Diversity and Functions - Ming Ni; Joe Atkinson; Erick Lundgren; Pablo Villalva; Wanben Wu; Jens‐Christian Svenning (Global Ecology and Biogeography, 2026)
Aim Large herbivores play key roles in ecosystems by promoting plant diversity, dispersing seeds, regulating nutrient cycling, and shaping vegetation structure. Since the Late Pleistocene, their declines have led to profound ecosystem changes. While often viewed as problematic, alien herbivores may partly compensate for these losses; yet their spatial contributions remain poorly understood. We provide the first spatially explicit assessment of native and alien large herbivores in North America (NA), evaluating their potential to restore herbivore diversity and functions relative to a present‐natural baseline. Location North America (United States and Canada). Time Period Late Pleistocene to present. Major Taxa Studied Ungulates ≥ 20 kg. Method We combined species distribution models based on citizen‐science records with functional trait data (body size, grazing, browsing) to estimate current and potential distributions of 12 native and 23 alien ungulate species. We compared four scenarios (current and potential natives, with and without aliens) against a present‐natural baseline. Results Alien ungulates are widespread, especially in southern NA, with Texas showing highest richness. If both native and alien species expanded to their climatic potential ranges, they could offset c. 40% of the deficit in richness and diet composition caused by Late Pleistocene extinctions, with full recovery possible in the Southeast and Arctic. Native species contribute about twice as much as alien species overall, but aliens disproportionately restore grazing intensity. Conclusions Alien ungulates can enhance herbivore diversity and partially restore lost ecosystem functions, though neither natives nor aliens fully compensate for extinct megafauna. Their tropical–subtropical origins limit potential ranges, and expansions must be balanced against ecological risks.